Tempo cognitivo e tempo social nas aulas de inglês para a envelhescência e terceira idade - Porto, Maria Augusta Rocha (2017)
Brazil will be considered the fifth largest worldwide country in number of elderly people next 2025, according to the prospection data by the Brazilian Institute of Geography and Statistics (IBGE, 2014). Beyond this, demographical density impact, demands for more studies at the socioeconomics, Health and Education areas begin to arise. National implemented Policy actions in Brazil as “The Aged People Decree 10.741, October 2003”, which aims with the social integration of the longevity people, may contribute with health quality of life, as learning a new language. We elicit for this thesis to verify the effect of time in social and cognitive dimensions into the English classes for the longevity groups: aging and elderly people. The social dimension refers for the social standard changings about being awareness on aging and expectancy and motivations in relation to the scholarships and for the workforce, once it interferes in the teaching and learning processes of a foreign language. The cognitive dimension time that interferes in the foreign learning involves the relation with language, in terms of physiology and its process. For measuring the effects of the cognitive and social timing into the English classes, we realized, in this thesis, three studies based on the data in two different classes as an extension course entitled. “The English class for the aging people”, at the first semester of 2016 length time at the Federal University of Sergipe. The first study aimed the reading time, into Portuguese and English languages, in a silent reading, and reading aloud, and the control of eye movement (the amount and the duration of fixation and go-past reading time) with three experimental groups in order to identify the effects of the aging in the participants. According to Cozijn; Vonker (2003), Rayner (2007), Dehaene (2012), the stablished standard for young speed readers, with fixation between 200 and 250 ms, that may get to 350 ms; for other types of group readers as aging and elderly people, the variability may overdo 500ms in both direct ways of reading (silent reading, reading aloud). The young participant group became different from the other groups, getting the standard of 200 to 250ms. The young group obtained a longer time in the English group than the Portuguese reading time. The elderly participant group showed a great number over the standard pattern of reading in 500ms, with the result of 600-650ms. In the English texts, the length time was over the standard one, between the three categories. The participants read the English texts in silent reading faster than the reading aloud texts. The second study aims to measure the planned and the executed length time of the extension course classes entitled “The English class for the aging people”, with the purpose of identifying the demand of time. Each class was planned with the acting of the documental control, in timing every minute from A1, A2, A3, A4, A5, A6, A7, A8, A9, A 10. The total global executed length time in both languages was inferior for the planned classes. The outcome for group -1, was 136, 6 min, with an average of 135, 2 min per class, the longer pedagogical activities that overdo were, A1, A2, A4, A7, A10. For group 2 the planned and the executed length time, the outcome was 116, 6 min for each class, with a longer length time for the activities A5, A6, A8. Considering the aims of the groups, the longer time difference is related for the social activities (emotional assessment and coffee break), for the pedagogical activities, the students demand longer time for the previous class reviews, word building, and extra activities which overdo the directed length time. In group 2, the activities that overdo the length time were direct for the silent reading and reading aloud, review the previous class, and discuss about both language culture. The third study, aimed to measure the emotional reactions of the aging participants, as well as elderly ones about the extension course “The English class for the aging people”, to verify the effects of the social time. Emotional test assessments were applied, in the beginning and at the end of the classes, with adjective words (time for learning) of course; to measure the satisfaction level on the participants of the English classes and analyze the reaction that the course motivates on the participants. The general outcomes show that although the aging studies demand a longer time for the executive functions, this demanding is not a hindrance for the participation in an English course. Our empiric study, with the analyses of reading time, eye-tracking, planning class length time, and emotional assessment charts contribute for the refining of the English course, with punctual outcome, that may be of use, for the implementation of the curricula components, pedagogical procedures for the adapted and evaluation of the printed and digital materials, as well as graduation course, and continuity studies, for the formation of the new teachers to be capable for a new workforce, as the aging and elderly people.________________________________________________________________________________________________________________________________